Formação de leitores no ensino médio com mediação tecnológica: desenvolvimento de habilidades de leitura - Domingues, Pura Moreno (2023)
This dissertation, entitled The formation of readers in High School with Technological Mediation: development of reading skills, is linked to the Postgraduate Program in Literature (MINTER), of the Institute of Humanities, Sciences, Education and Creativity, of the University of Deep step. The research developed was guided by the following question: how does the Reading Club Project contribute to the development of reading skills of indigenous, quilombola, riverside, rural and urban students in the 1st year of High School with Technological Mediation? As a general objective, we sought to analyze the contribution of the Reading Club Project to improving reading competence, aligned with the guiding axis of reading and writing, in light of the National Common Curricular Base (BNCC). As specific objectives, it was established: to verify whether the guidelines of the Reading Club Project documents encourage the demand for the reading and writing axis of the National Common Curricular Base; suggest teaching guidelines that develop the autonomy and skills necessary for reading different literary texts; investigate the challenges and perspectives of reading literary texts to train readers with a cultural, social and critical vision. This is qualitative research, of a bibliographic nature in which, firstly, a theoretical-methodological review was developed regarding the development of language and the Portuguese language component in the reading practice axis in High School, in the light of the BNCC, the Reference Curriculum of Rondônia, the National Curricular Parameters, as well as laws, decrees, resolutions, ordinances and others. As an object of analysis, the Instructional Plan of the Reading Club Project was taken, considering the following criteria: motivation, introduction, reading and interpretation (Cosson, 2014). The theoretical framework was based on the studies of Kleiman (2000, 2008, 2013), which discusses reading and reader formation; Candido (1995), Rojo (2009, 2013) and Soares (2009), who deal with literacy as a way of using reading and writing with a social foundation for the production and construction of texts. In relation to dialogical discourse, Bakhtin (2011) was used, which points out relevant aspects for understanding the concept of language and its implications for reading practices. Finally, the contributions of Belloni (2012), Masetto (2013) and Kenski (2007, 2012) regarding the specificities of technology-mediated education and the challenges of this teaching modality. The results indicate that the Reading Club Project emerges as an effective instrument for improving the reading skills of 1st year high school students. Through the integration of literature, technology and pedagogy, the project not only boosts reading proficiency, but also contributes to the formation of critical, participatory individuals prepared to face the challenges of contemporary society.